Analysis of Pluralism Ideas of Muhammad ‘Ali Ash-Shabuni in the Tafsir of Rawa’i al-Bayan - Ahmad Dimyati; Nur Khoiriyah (Santri: Journal of Pesantren and Fiqh Sosial, 2020)
This study aims to reconstruct Muhammad 'Ali Ash-Shabuni's idea of ​​pluralism in the tafsir of Rawa'i al-Bayan. Ash-Shabuni's idea of ​​pluralism is interesting because it is based on the interpretation of the verses of war. The study of war verses has implications for shaping the ethics that must be enforced in the most extreme forms of interaction, war. The reconstruction of Ash-Shabuni 's pluralism idea was designed in qualitative research with an analytical descriptive type. While the approach used is semantic content-analysis, because the data is in the form of a tafsir book. As a sample, interpretations of surah al-Baqarah verses 190-195 were taken will which is discussed the provisions of war, and verses 216-218 with the theme of the law of war in the haram months. Based on semantic content analysis, it can be concluded that basically, Islamic teachings invite acceptance of non-Muslims. The warfare that is allowed in Islam is as a defense method against agreements that are violated by non-Muslims, defending the land of haram (as the land of birth), defense of the haram months as a form of respect for tradition, the war for defending Allah's religion, and war because it avoids slander in the form of coercing infidels so that Muslims apostatize.